(untitled) (Práxis Educativa, 2025)
This article critically examines the epistemic challenges of contemporary democracies and proposes the ethical use of artificial intelligence (AI) as a means to strengthen informed democratic practices, aligning them with certain ideals of epistocracy. Drawing on Plato’s classical critique of democracy and the contemporary defense of epistocracy by authors such as Jason Brennan, the article discusses the cognitive limitations that affect the quality of political decisions—including rational ignorance, polarization, cognitive biases, and disinformation—and how these undermine both the legitimacy and the effectiveness of elected governments. Instead of adopting an elitist and exclusionary epistocracy, the article advocates for a more informed democracy, one that combines the democratic ideal of equality with expanded and assisted access to relevant knowledge for political deliberation. AI is presented as a potential ally in this effort, functioning as an enabling infrastructure. The article also critically analyzes the risks of AI, including algorithmic bias, informational manipulation, and the reproduction of inequalities, advocating for an approach attentive to the normative consequences of this technology. Finally, it argues that a more just and informed democracy will only be possible if technologies such as AI are conceived as tools of epistemic justice, oriented not toward replacing but rather strengthening citizens’ autonomous political judgment. Keywords: Democracy. Epistocracy. Artificial intelligence.